The podosphaera fusca TUB2 gene, a molecular "swiss army knife" with multiple applications in powdery mildew research - Vela-Corcía, David; Bellón-Góme, Davinia; Lopez-Ruiz, Francisco; Tores, Juan; Perez-Garcia, Alejandro (Elsevier Ltd., 2014)
The powdery mildew fungus Podosphaera fusca (synonym Podosphaera xanthii) is the main causal agent of cucurbit powdery mildew and one of the most important limiting factors for cucurbit production worldwide. Despite the fungus' economic importance, very little is known about the physiological and molecular processes involved in P. fusca biology and pathogenesis. In this study, we isolated and characterised the β-tubulin-encoding gene of P. fusca (PfTUB2) to develop molecular tools with different applications in powdery mildew research. PfTUB2 is predicted to encode a protein of 447 amino acid residues. The coding region is interrupted by six introns that occur at approximately the same positions as the introns present in other fungal TUB2-like genes. Once cloned, the PfTUB2 sequence information was used in different applications. Our results showed that the TUB2 gene is a good marker for molecular phylogenetics in powdery mildew fungi but it is unsuitable for the analysis of intraspecific diversity in P. fusca. The expression of PfTUB2 was proven to be stable in different temperature conditions, supporting its use as a reference gene in quantitative gene expression studies. Furthermore, an allele-specific PCR assay for the detection of resistance to methyl-2-benzimidazole carbamate (MBC) fungicides in P. fusca was developed based on the correlation between the single amino acid change E198A in β-tubulin and the MBC resistance phenotype. Lastly, PfTUB2 was used as a target gene in the development of a high-throughput method to quantify fungal growth in plant tissues.